Bacteria isolated from blood cultures in a neonatal and pediatric intensive care unit and their antibiotic resistance: 5-year results - Zerife Orhan; Arzu Kayış; Özlem Kirişci; Burak Küçük; Mehzat Altun; Murat Aral (Trends in Pediatrics)
Objective: Bloodstream infections represent a leading cause of illness and death among children in developing nations. The aim of this study was to determine the bacterial profile and antibiotic resistance status of pathogens isolated from blood cultures taken from children in the neonatal and pediatric intensive care units of a university hospital in Türkiye.